The Strategy of Learning Innovation Improvement through the MBKM Program at STIP Jakarta; Empirical Study - A. Chalid Pasyah; Retno Sawitri Wulandari; Vidya Selasdini (Dinasti Publisher, 2024)
This emphirical study aims to identify the learning innovation improvement strategy through the MBKM program at STIP Jakarta. The literature research technique was used to conduct this study, and information was gathered through literature references, pertinent observations and documentation, interviews with members of the Academic Division, as well as other studies on the MBKM policy. Merdeka Belajar Kampus Merdeka (MBKM), a self-study independent campus project of the Government of Indonesia through the Ministry of Education, Culture, Research and Technology, enables students to explore their talents and interests outside of academic learning. This program is a part of a larger endeavor that has two parts: Merdeka Belajar, which encourages talent and autonomous study and Kampus Merdeka, which offers contextual field experiences to enhance skills and prepare students for the future. According to the study's findings, the MBKM program's implementation at STIP had not been as effective as it could have been because only three out of eight types of off-campus learning—research, internships/work experiences, and humanitarian projects—had been completed, while five more were still being worked on through the management policy process. In order for students to attain the best learning outcomes and to constantly be relevant in terms of attitude, knowledge, and skills, STIP must develop policies and execute innovative learning methods. The Kampus Merdeka is an independent and adaptable organization that promotes a creative learning environment that doesn't restrict and fits the demands of cadets, which in turn has implications for improving the quality of STIP education.